Conception and development of a neurological registry of patients with persistent health impairments following work-related COVID-19 disease in Germany - Schwenkreis, Peter; Kozak, Agnessa; Gonschorek, Andreas; Schmehl, Ingo; Seddigh, Susann; Fürst, Andrea; Wohlfahrt, Kai; Rademacher, Corinna; Engel, Lynn; Wefers, Jacob; Kobes, Kerrin; Kleinmüller, Olaf; et al. (GMS Hygiene and Infection Control)
Background: Healthcare and social workers had an increased occupational risk of contracting SARS-CoV-2 during the pandemic. Some developed long-lasting symptoms known as post-COVID syndrome (PCS). To assess the consequences of COVID-19 for individuals insured by the German Social Accident Insurance, the BG hospitals (Berufsgenossenschaftliche Kliniken: clinics for occupational accident insurance) established an interdisciplinary diagnostic programme. Data collected during routine clinical practice are transmitted to a multicenter post-COVID registry to enhance knowledge of the long-term consequences related to COVID-19 and to optimize diagnostics, treatment, and rehabilitation. The design of the post-COVID registry, along with a description of the study population, is detailed in this paper.Methods: The registry includes patients with an occupational disease or accident. Depending on the severity and complexity of the symptoms, patients received an outpatient post-COVID examination or an inpatient post-COVID check (PCC). The collected data comprise demographics, occupational and social history, disease progression, pre-existing conditions, utilization of health services, persistent symptoms, and psychosocial and neuropsychological assessments. Further investigations are carried out in response to symptoms and needs, using clinical assessment, instrumental and imaging techniques, as well as questionnaires. In addition, serum and cerebrospinal fluid samples are preserved for biomarker analysis.Results: By September 2024, 1,957 patients from six BG hospitals were included. An interim analysis of 1,150 cases shows that patients are predominantly female (77%) and the average age is 51 years (standard deviation [SD] 10.5). Around 43% worked in nursing at the time of infection. In 63% of cases, an inpatient post-COVID check was carried out. About 20% were hospitalized during acute COVID-19 infection, with an average stay of 14.6 days (SD 18.4). More than half were still unable to work at the time of examination, with no significant differences between hospitalized and non-hospitalized patients. Common pre-existing conditions included heart disease (48%), allergies (45%), and lung disease (33%). PCS symptoms mainly consisted of reduced physical capacity (95%), concentration difficulties (79%), and shortness of breath (69%). 81% had previously received outpatient and/or inpatient rehabilitation.Conclusion: The outpatient and the inpatient PCC are essential in managing the recovery process for patients with PCS. Data analysis will provide insights into the need for medical care and rehabilitation. In addition, longitudinal analyses will be used to track the progress of the post-COVID registry over time and monitor the effectiveness of the recommended measures.